2023
DOI: 10.1039/d3fo00286a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis detected multiple pathways by which pomegranate punicalagin exerts its biological effects in modulating host–microbiota interactions in murine colitis models

Abstract: As one of the key bioactive food ingredients in pomegranate, punicalagin (PA) is known to possess wide-ranging functional activities. However, few studies have focused on its fate and physiological relevance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…This finding indicates that astaxanthin does not function by restoring the gut flora structure in pseudo-sterile mice. 23,24 Instead, it is advisable to concentrate on the variations in dominant species within the gut flora. We subsequently conducted an analysis of the key differential microorganisms in the two groups of mice.…”
Section: Disscusionmentioning
confidence: 99%
“…This finding indicates that astaxanthin does not function by restoring the gut flora structure in pseudo-sterile mice. 23,24 Instead, it is advisable to concentrate on the variations in dominant species within the gut flora. We subsequently conducted an analysis of the key differential microorganisms in the two groups of mice.…”
Section: Disscusionmentioning
confidence: 99%
“…Briefly, a QIAamp Fast DNA Stool Mini Kit (Qiagen) was used with some modifications. 21 Gel electrophoresis was used to monitor the concentration and evaluate the purity of DNA. The hypervariable V3-V4 regions of the 16S rRNA gene were sequenced with specific primers (forward primer, 341F: CCTAYGGGRBGCAS CAG; reverse primer, 806R: GGACTACNNGGGTATCTAAT) tagged with barcodes.…”
Section: Microbiome Studies Using 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…However, the association was not established in stool on a mice model 53 . An in vivo study analyzing feces has recently found lower amounts of 3-MH and anserine (see section 3.2.2) in patients with irritable bowel syndrome 56 .…”
Section: Amino Acids and Derivatesmentioning
confidence: 99%
“…but not in plant analogs. Gamma-glutamyl transpeptidase (GGT) is a group of enzymes that catalyzes the transfer of the gamma-glutamyl group from gamma-glutamyl peptides to other peptides or free amino acids, and it is believed to be responsible for many physiological disorders in mammals, such as oxidative stress and gut inflammation 56 . In humans, these enzymes are primarily present in biliary epithelial cells but can also be present in prokaryotic cells 69 .…”
Section: Dipeptides and Derivativementioning
confidence: 99%